Innovation in Later Life: A Study of Grandmothers and Facebook. (June 2021) - Yachin, Mor; Nimrod, Galit
Relying on the Innovation theory of successful aging, this study aims at exploring how grandmothers around the world perceive and use Facebook. Twenty-seven focus groups were set up in seven countries: Canada, Colombia, Israel, Italy, Peru, Romania, and Spain. Participants consisted of 184 grandmothers aged 65 and over who use information and communication technology to some extent. Data were analyzed according to hybrid thematic analysis principles and findings pointed to substantial ambivalence regarding Facebook. Grandmothers who used it reported rather restrained use that was typically triggered externally and characterized by reactive use patterns. Nevertheless, Facebook appeared to promote users' well-being by supporting preservation of their relationships, roots, and sense of relevance. These findings suggest a new theoretical tenet to innovation theory according to which even "restrained innovation" in later life may be beneficial.